Cassia tora Seed Extract and Its Active Compound Aurantio-obtusin Inhibit Allergic Responses in IgE-Mediated Mast Cells and Anaphylactic Models - Kim, Myungsuk; Lim, Sue Ji; Lee, Hee-Ju; Nho, Chu Won (AMER CHEMICAL SOC, 2015)
Cassia tora seed is widely used due to its various biological properties including anticancer, antidiabetic, and anti-inflammatory effects. However, there has been no report of the effects of C. tora seed extract (CTE) on immunoglobulin E (IgE)mediated allergic responses. In this research, we demonstrated the effects of CTE and its active compound aurantio-obtusin on IgE-sensitized allergic reactions in mast cells and passive cutaneous anaphylaxis (PCA). CTE and aurantio-obtusin suppressed degranulation, histamine production, and reactive oxygen species generation and inhibited the production and mRNA expression of tumor necrosis factor-a and interleukin-4. CTE and aurantio-obtusin also suppressed the prostaglandin E-2 production and expression of cydooxygenase 2. Furthermore, CTE and aurantio-obtusin suppressed IgE-mediated Fc epsilon RI signaling such as phosphorylation of Syk, protein kinase C mu, phospholipase C gamma, and extracellular signal-regulated kinases. CTE and aurantio-obtusin blocked mast cell-dependent PCA in IgE-mediated mice. These results suggest that CTE and aurantio-obtusin are a beneficial treatment for allergy-related diseases.
Keywords: IN-VITRO; ANTHRAQUINONE; RBL-2H3; DEGRANULATION; ACTIVATION; RELEASE; L.; GENERATION; OXIDANTS; PATHWAY